Mener une enquête empirique sur la force policière excessive en Allemagne: méthode, réalisation et enjeux du projet de recherche "Coups et blessures par un dépositaire de l’autorité publique" - Abdul-Rahman, Laila (Déviance et société, 2021)
In Germany, proceedings against police officers for assault and battery by a public official are frequently dismissed for lack of sufficient charges and only very rarely go to trial. The judicial practice is characterised by a low conviction rate. Based on these findings from the official crime control statistics, the research project methodically addresses the issue of victims of police violence in Germany for the first time and examines the situational and individual factors of victimisation and its treatment in court. In addition to the statistically recorded cases, the focus is on the dark figure of this specific area of crime. This article outlines the methodological approach of the study and analyses the strategy for recruiting survey participants, by means of a snowball effect via gatekeepers and intensive use of social media. It examines and evaluates the methodological challenges raised by the research project and provides an overview of the initial results.